DIVERSIFIKASI PRODUK SUSU PASTEURISASI DENGAN PENAMBAHAN SARI BUAH JAMBU BIJI MERAH (Psidium gujava Linn) - Fitasari, Puspa; Syahrir, Mardi; Mustarin, Amirah (Universitas Negeri Makassar, 2018)
study aims to determine the effect of red guava juice (Psidium gujava Linn) on the content of vitamin C in the manufacture of pasteurized milk, and the level of panelist's preference for pasteurized milk. The type of this research is quantitative research with experimental approach using Completely Randomized Design (RAL) consisting of control treatment that is without addition of red guava juice, 3% treatment, 6% treatment, and 9% treatment. The results showed that in the chemical test the highest content of vitamin C was the control treatment without the addition of red guava juice. The results of organoleptic test showed that the best treatment on taste, aroma and color indicator was on the treatment of 6% red guava juice and 500 ml of milk.